The handing over by the South African Police Services (SAPS) and outcome of suspected mentally ill patients at Chris Hani Baragwanath Hospital (CHBH) - Jonsson, Gregory Wayne (My University, 2009)
AIM: To study the process of handing over custody by South African Police Service (SAPS) of suspected mentally ill patients at Chris Hani Baragwaneth Hospital (CHBH) and the outcome of such patients. METHODS: The study was a retrospective record review of patients, 18 years and older, referred by SAPS to the Emergency Department at CHBH. Completed MHCA Form 22, during the period July 2007 to December 2007, were obtained from the hospital records. The forms were analysed to determine the compliance of SAPS and the medical practitioners in completing these forms. Demographics and clinical characteristics, and the final outcome of the study population were obtained from the hospital notes. RESULTS: During the study period, 708 of the 718 patients handed over by SAPS to the emergency department of CHBH had Form 22’s, 579 (81.78%) of the patients were males. The majority of patients were between the age 26 - 50 years (65.39%); unemployed (80.23%), achieved a Grade 10 or lower level of education (55.65%) and were single (84.32%). 378 (53.39%) patients had previously abused substances, 47 (6.64%) had a forensic history and 552 (77.97%) had a past psychiatric illness. SAPS officials had correctly completed 86.16% of the forms, whilst the medical practitioners had only correctly completed 9.89% of the forms. Of the 718 patients handed over by SAPS and admitted to the medical admissions ward, 319 (44.06%) were discharged for outpatient care, whilst only 272 (38.42%) were admitted to the psychiatric ward for further inpatient psychiatric care and 102 (14.41%) admitted to the medical wards for further inpatient medical care. CONCLUSION: The findings indicate that the SAPS are better at complying with the regulations of the Mental Health Care Act as compared to the health care professionals in the emergency department of CHBH. It is recommended that improved assessment at the emergency department would reduce the number of admissions and costs to the already resource constrained hospital.
M.Med.(Psychiatry), Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: mental illness